The impact of patient protection and Affordable Care Act on trauma care: A step in the right direction. Issue 3 (September 2016) - Joseph, Bellal; Haider, Ansab A.; Azim, Asad; Kulvatunyou, Narong; Tang, Andrew; O'Keeffe, Terence; Latifi, Rifat; Green, Donald J.; Friese, Randall S.; Rhee, Peter
Abstract : INTRODUCTION: The Patient Protection and Affordable Care Act (ACA) was implemented to guarantee financial coverage for health care for all Americans. The implementation of ACA is likely to influence the insurance status of Americans and reimbursement rates of trauma centers. The aim of this study was to assess the impact of ACA on the patient insurance status, hospital reimbursements, and clinical outcomes at a Level I trauma center. We hypothesized that there would be a significant decrease in the proportion of uninsured trauma patients visiting our Level I trauma center following the ACA, and this is associated with improved reimbursement. METHODS: We performed a retrospective analysis of the trauma registry and financial database at our Level I trauma center for a 27-month (July 2012 to September 2014) period by quarters. Our outcome measures were change in insurance status, hospital reimbursement rates (total payments/expected payments), and clinical outcomes before and after ACA (March 31, 2014). Trend analysis was performed to assess trends in outcomes over each quarter (3 months). RESULTS: A total of 9, 892 patients were included in the study. The overall uninsured rate during the study period was 20.3%. Post-ACA period was associated with significantly lower uninsured rate ( p < 0.001). During the same time, there was as a significant increase in the Medicaid patients ( p = 0.009). This was associated with significantly improved hospital reimbursements ( p < 0.001). On assessing clinical outcomes, there was no change in hospitalization ( p = 0.07), operating room procedures ( p = 0.99), mortality ( p = 0.88), or complications ( p = 0.20). Post-ACA period was also not associated with any change in the hospital ( p = 0.28) or length of stay at intensive care unit ( p = 0.66). CONCLUSION: The implementation of ACA has led to a decrease in the number of uninsured trauma patients. There was a significant increase in Medicaid trauma patients. This was associated with an increase in hospital reimbursements that substantially improved the financial revenues. Despite the controversies, implementation of ACA has the potential to substantially improve the financial outcomes of trauma centers through Medicaid expansion. LEVEL OF EVIDENCE: Economic and value-based evaluation, level III. Abstract : Supplemental digital content is available in the text.